2021
DOI: 10.1001/jamanetworkopen.2021.11398
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Sex Hormones With Inflammation and Disease Severity in Patients With COVID-19

Abstract: IMPORTANCE Male sex is a risk factor for developing severe COVID-19 illness. It is not known whether sex hormones contribute to this predisposition. OBJECTIVE To investigate the association of concentrations of serum testosterone, estradiol, and insulinlike growth factor 1 (IGF-1, concentrations of which are regulated by sex hormone signaling) with COVID-19 severity. DESIGN, SETTING, AND PARTICIPANTS This prospective cohort study was conducted using serum samples collected from consecutive patients who present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
154
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(182 citation statements)
references
References 57 publications
19
154
1
8
Order By: Relevance
“…In accordance with this hypothesis, recent work has correlated lower level of testosterone in males to worse prognosis when dosed during COVI-19. 32 This reinforces the better outcomes observed in this population with proxalutamide.…”
Section: Discussionsupporting
confidence: 72%
“…In accordance with this hypothesis, recent work has correlated lower level of testosterone in males to worse prognosis when dosed during COVI-19. 32 This reinforces the better outcomes observed in this population with proxalutamide.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, an inverse association between testosterone concentrations and disease severity in male but not female COVID-19 patients was reported [ 1 ]. COVID-19 is characterized by systemic inflammation and men are more likely to be severely affected than women.…”
mentioning
confidence: 99%
“…Furthermore, there is evidence that in patients with respiratory tract infections without COVID-19, TT levels were higher than in patients with COVID-19 infection, but both groups had lower levels of TT compared with the control group [ 42 ]. A recent cohort study by Dhindsa et al on 90 males and 62 females with COVID-19 revealed that lower testosterone levels in males were associated with increased severity of COVID-19, inflammatory markers and disease-related mortality [ 43 ]. Another study also demonstrated that low TT and calculated free testosterone at admission were associated with poor outcomes [ 44 ].…”
Section: Resultsmentioning
confidence: 99%